Effect of Glycerin on Stability and Antioxidant Activity of Ethyl Acetate Fraction of Secang Wood Face Mist - Nur Halisa Rahmawati; Nastiti Utami; Dian Puspitasari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Secang wood (Caesalpinia sappan L.) is a plant that contains brazilin, a natural antioxidant. A potential problem in the brazilin formulation process is that brazilin becomes unstable due to environmental influences. Face mist is one of the formulations that contains glycerin to maintain the stability. Glycerin can stabilize brazilin by forming hydrogen bonds between glycerin and brazilin. Objective: The main objective of this research was to evaluate the effect of glycerin on the physical stability and antioxidant activity in ethyl acetate fraction of secang wood face mist. Methods: Face mist formulation was prepared using different glycerin concentrations, such as F1 (10%), F2 (15%), and F3 (20%). Face mist was formulated using ethyl acetate fraction of secang wood, glycerin, phenoxyethanol, and aquadest. Physical evaluation stages included organoleptic, homogeneity, pH, specific gravity, viscosity, spray spreadability, skin moisture, cycling tests, and hedonic tests. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method was used to examine antioxidant activity. Results: The physical evaluation showed that face mist produced good results and complied with the requirements of face mist. The antioxidant activity test showed that face mist with the IC50 value for F1 was 22.114±0.046 µg/mL, F2 was 21.828±0.033 µg/mL, and F3 was 21.378±0.025 µg/mL. Conclusion: Based on these observations, the best formula was F3 because the antioxidant activity was classified as very strong, and the physical evaluations were considered more stable than others. In addition, F3 had the highest average score on the hedonic test.